Barriers of Effective Political Communication and Youth Behavior during 2022 Elections in Kisumu County, Kenya - Wandaga, John; Inimah, Musuruve Gertrude; Mathooko, Petronilla Mbartha (International Journal of Communication and Public Relation, 2025)
Purpose: The study sought to establish barriers of effective political communication and youth behavior during 2022 elections in Kisumu County, Kenya. The existing gap in knowledge was the understanding of how barriers of effective political communication can influence youth behavior during election campaigns. Methodology: The study was conducted using the descriptive design, with the mixed methods approach. Quantitative data was collected from 400 respondents of Kisumu County, Kenya, while qualitative data obtained through 10 in-depth interviews and 30 respondents for Focus Group Discussions. Findings: The study findings revealed that even though youth play a critical role in various stages in future leadership, they can be used as a source of unity as well as source of division. If youth are not used productively during electioneering periods, they have negative impact on themselves, families and society at large affecting voter turnout, voting trends and inter-ethnic relationships. The study further found that barriers of effective political communication influence youth behavior. Unique Contribution to Theory, Practice and Policy: The study was informed by Speech Act Theory, Theory of Political Propaganda and Mediatization of Politics Theory.The study recommends the need for political class to follow laid down legislations by avoiding the use of barriers of effective political communication for proper youth engagement in political matters without causing mayhem among themselves in the society through use of hate, propaganda, stereotype and discriminatory political messages.